Influence of age, farming site, and boiling on pro-vitamin A content in sweet potato (Ipomea batatas (L.) Lam.) storage roots - K'Osambo, L.M.; Carey, E.E.; Misra, A.K.; Wilkes, J.; Hagenimana, V. (Elsevier, 1998)
To maximize the availability of pro-vitamin A carotenoids in sweet potato and to recommend the appropriate start of piecemeal harvesting practice, the main carotenoids in storage roots of 17 different sweet potato cultivars were surveyed using HPLC and spectrophotometry methods, and their variation due to production site, storage root age, and boiling was assessed. There was significant variation in carotenoid content among cultivars. Six different carotenoids were consistently detected in significant quantities. Orange-fleshed roots contained higher total carotenoid and Beta-cartotene content than white- and cream-fleshed lines, and all trans-Beta-carotene predominanted. The effect of storage root age on carotenoid content was significant. Twelve weeks after planting, the yield and amount of pro-vitamin A present in roots of orange-fleshed cultivars evaluated were high enough to provide adequate dietary pro-vitamin A and suggest the start of piecemeal harvesting. The effect of farming site on total carotenoids was significant; however, the amount of Beta-carotene was not different over three testing sites. Boiling of roots for 30 min caused a reduction in total carotenoids which varied by cultivar, however, further boiling for up to 60 min did not exacerbate the reduction in total carotenoids.